At-home dried blood spot (DBS) collection to increase population heterogeneity representation in pediatric research: An ECHO study - Green, Joseph M.; Barry, Fatoumata; Burton, Phoebe; Beauchemin, Jennifer; Huentelman, Matthew J.; Deoni, Sean C. L.; Lewis, Candace R.; , on behalf of program collaborators for Environmental Influences on Child Health Outcomes (Frontiers in Pediatrics, 2023)
Self-collection of dried blood samples (DBS) in the participant’s home is an alternative to university/hospital visits for research and has the potential to improve population heterogeneity representation in research. This study aimed to assess feasibility of guardian and/or self-DBS collection in healthy youth in the lab and home. Guardians/youth [N = 140; females = 63; Mage = 8.73, SDage = 3.56] enrolled in a longitudinal study of typical development were asked during a lab visit to provide a DBS. Upon providing a sample, participants were asked if they would be willing to self-collect in the home and return the sample via the post-office. Of those asked to provide a sample in lab, 82% consented and 18% declined, with a significant difference in age but no significant difference in sex, ethnicity, race, or family income. Of those who provided a sample in lab, 75% were willing to self-collect DBS in the home, with no significant difference in demographic variables between them. We report a quality assessment and DNA extraction results from a subset of samples. Results demonstrate high feasibility of DBS collection from healthy youth for research purposes both in the laboratory and at home across different demographic variables. Developmental researchers should consider including this approach to increase population heterogeneity representation into their studies.